1874 N.J. Laws 137-38 - (:unkn) unknown (My University, 1874)
Ch. 525, 4: That no person shall at any time kill any wild duck, brant, or goose with any device or instrument known as a swivel or punt gun, or with any gun other than such guns as are habitually raised at arms [sic] length and fired from the shoulder; or shall use any net, device, instrument, or gun other than such gun as aforesaid with intent to capture or kill any such wild duck or goose, under a penalty of fifty dollars.
Keywords: HUNTING REGULATION